Extensively Drug-Resistant Hypervirulent Klebsiella pneumoniae From a Series of Neonatal Sepsis in a Tertiary Care Hospital, India - Banerjee, Tuhina; Wangkheimayum, Jayalaxmi; Sharma, Swati; Kumar, Ashok; Bhattacharjee, Amitabha (Frontiers in Medicine, 2021)
The recent emergence of multidrug-resistant (MDR) Klebsiella pneumoniae with hypervirulent traits causing severe infections and considerable mortality is a global cause for concern. The challenges posed by these hypermucoviscous strains of K. pneumoniae with regard to their optimal treatment, management, and control policies are yet to be answered. We studied a series of extensively drug-resistant (XDR) and hypervirulent K. pneumoniae ST5235 isolates with resistance to carbapenems and polymyxins causing neonatal sepsis in a tertiary care hospital in India. A total of 9 K. pneumoniae isolates from 9 cases of neonatal sepsis were studied with respect to their clinical relevance, antimicrobial susceptibility profile, presence of extended spectrum β lactamase (ESBL) production, and responsible genes, carbapenemases (classes A, B, and D), and aminoglycoside-resistant genes. Hypervirulence genes encoding hypermucoid nature, iron uptake, and siderophores were detected by multiplex PCR. The plasmid profile was studied by replicon typing. Isolates were typed by multilocus sequence typing (MLST) and enterobacterial repetitive intergenic consensus (ERIC) PCR to study the sequence types (STs) and clonal relation, respectively. The neonates in the studied cases had history of pre-maturity or low birth weight with maternal complications. All the cases were empirically treated with piperacillin–tazobactam and amikacin followed by imipenem/meropenem and vancomycin and polymyxin B as a last resort. However, all the neonates finally succumbed to the condition (100%). The studied isolates were XDR including resistance to polymyxins harboring multiple ESBL genes and carbapenemase genes (blaNDM and blaOXA−48). Hypervirulence genes were present in various combinations with rmpA/A2 genes present in all the isolates. IncFI plasmids were detected in these isolates. All belonged to ST5235. In ERIC PCR, 6 different clusters were seen. The study highlighted the emergence and burden of XDR hypervirulent isolates of K. pneumoniae causing neonatal sepsis in a tertiary care hospital.